Ultrasound Assessment of Entheseal Sites and Anterior Chest Wall in Ankylosing Spondylitis: A Cross‐Sectional Study - Xie, Haiqin; Zhou, Gengmin; Luo, Haiyu; Zhao, Chenyang; Zhang, Yusen; Dong, Qian; Lv, Heng; Zhong, Jianqiu; Lv, Jiyang; Zhang, Weiwei; Sun, Desheng; Wang, Qingwen; et al. (Journal of ultrasound in medicine, 2023)
The study was designed to evaluate entheseal sites and anterior chest wall (ACW) of patients with ankylosing spondylitis (AS) using ultrasound (US) and investigate the correlation between disease activity and US score. This prospective cross-sectional study included 104 patients with AS and 50 control subjects. Each patient underwent US scanning of 23 entheses and 11 sites of the ACW. The US features, including hypoechogenicity, thickness, erosion, calcification, bursitis, and Doppler signal, were evaluated. Disease activity was assessed based on C reactive protein (CRP), erythrocyte sedimentation rate (ESR), disease activity score-C reactive protein (ASDAS-CRP), and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). The most commonly involved entheses on US were the Achilles tendon (AT) and quadriceps tendon (QT). The most involved site of ACW was the sternoclavicular joint (SCJ). Compared with the control group, significant differences were observed in the AS group in the rates of US enthesitis and ACW in AT (P = .01), SCJ (P = .00), and costochondral joint (CCJ) (P = .01). Patients with high or very high disease activity had a higher erosion score (P = .02). The erosion score was weakly positively associated with CRP, ESR, BASDAI, ASDAS-CRP, and ASDAS-ESR (correlation coefficient: 0.22-0.45). The most commonly involved entheseal sites on US were AT and QT, while the site of ACW was SCJ. The US assessment of AS should take the ACW into account. High disease activity might indicate erosion in AS.